IMPROVING TEACHERS' ACADEMIC WRITING PROFICIENCY IN MEMPAWAH THROUGH MGMP TRAINING: ACTION RESEARCH - Ulfah, Maria; Karolina, Venny (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
This action research-based writing training is part of a research project organized by instructors in the field of social studies at the Faculty of Teacher Training, Tanjungpura University. The training applied an action research methodology, involving multiple cycles, each encompassing planning, execution, observation, and reflection stages. This particular approach was selected to encourage participants to share their insights for the purpose of enhancing the training's quality. The primary objective of this research was to gather feedback from teachers, along with their recommendations, to improve the effectiveness of academic writing training that is rooted in action research. The study involved 40 secondary school teachers who were in a group of MGMP Mempawah and took place at SMPN 1 Mempawah. Data was collected through the use of an open-ended questionnaire. The findings indicated that teachers encountered difficulties in finding enough time for writing and accessing online resources. As a result, they suggested extending the duration of the training. Furthermore, they proposed the provision of more comprehensive information and examples for each section of the research article. Finally, it was noted that teachers had a positive perception of the training.